Transportation Needs of Older Adults in Suburban and Rural Areas - (:unkn) unknown (My University, 2023)
The fact that the average age of the world's population is increasing, which is more pronounced in developed countries, necessitates the understanding of the challenges faced by older adults in accessing transportation services. With advancing age, individuals may experience age-related changes that can notably affect their driving capabilities, emphasizing the importance of alternative transportation alternatives. This challenge is more evident in suburban and rural settings, where transportation choices are limited, and older adults often find themselves without access to suitable transportation alternatives. Given that mobility plays an essential role in maintaining social connections, accessing healthcare services, and fulfilling daily needs, gaining a comprehensive understanding of the unique challenges faced by older adults in accessing transportation services in these areas is pivotal. This study employed a multifaceted approach, incorporating questionnaire surveys and focus group meetings with participation from both older adults and transportation service providers in suburban and rural Wisconsin. The dataset included 1,650 valid questionnaire responses from older adults, addressing their socio-demographics, technology usage, travel patterns, satisfaction with local transportation, challenges faced, and suggestions for improvements. The majority of responses were from females, individuals from low-income households, and those living alone. Furthermore, 103 valid responses were received from service providers, echoing and expanding upon these topics from a different perspective. Regression models were applied to analyze older adults' travel mode and purpose preferences. Qualitative insights into their experiences and recommendations were obtained through focus meetings conducted with both older adults and service providers. The analyses unveiled that older adults often depend on self-driving and support from their social networks, while their utilization of local transportation services remains limited. The model results further confirmed the influence of demographic factors, demonstrating fewer trips among females, adults over 85 years, wheelchair users, low-income individuals, and those living alone. The COVID-19 pandemic curtailed older adults’ mobility additionally. A pronounced digital divide underscored the need to address internet access issues. Ride requests were primarily made via phone calls. While overall satisfaction with local services was positive, concerns regarding scheduling, routes, accessibility, healthcare coordination, reservations, communication, and driver performance were prevalent, highlighting areas for improvement in elderly transportation services. To address the found transportation barriers, this study puts forward eight key recommendations: collaboration and funding, coordination, expanding services, enhancing accessibility, providing training, focusing on rural areas, targeted marketing, and technology improvement. These measures have the potential to significantly enhance transportation services for older adults, benefiting not only Wisconsin but also comparable suburban and rural regions. Policymakers, transportation providers, and community organizations can utilize these insights to establish a more inclusive, accessible, and age-friendly transportation network that promotes the well-being of older adults.
Keywords: older adults; rural transit; transportation-disadvantaged